Tourist industry globalization - Dragiša Radojković (Mенаџмент у хотелијерству и туризму, 2013)
The world has become a global community, making thus many destinations reachable which was inconceivable a few decades ago. Many world industries are being dominated today by a relatively small number of competitors that are in possession of the majority of market share. It is often difficult, even impossible for a large number of prosperous competitors to enter those markets. There are also market leaders in the world touristic industry. However, in 2002 top ten world destinations represented less than a half of the overall touristic market. The World Touristic Organisation (WTO) claims to have placed on record 70,000,000 new international tourists in 2004. Tourism is a global business whose market is ever enlarging one. Touristic market is open to new entrances, so new destinations may gain their market share and enjoy the economic and social benefits tourism offers.